Analisis Faktor-Faktor yang Mempengaruhi Perdagangan Indonesia dengan Negara-Negara Anggota APEC - Dona Putri Cahyaningtyas (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2020)
This study aims to analyze the factors that influence Indonesia's trade with APEC member countries. Research period between 2011-2017. The method used in conducting the analysis is the Gravity Model. To support the conclusion of the gravity model, the Trade Conformity Index and the Grubel Lloyd Index are also calculated. Based on the results of the study showed that Indonesia's trade with APEC member countries was positively influenced by GDP, exchange rates, and Trade Conformity Index, while economic distance and population had a negative effect. It shows that Indonesia's trade with APEC member countries has an inter-industry trade pattern which is indicated by a positive sign of the coefficient of TCI and relatively low GLI values. But it should be noted that quite a lot of Indonesian commodities have Grubel Lloyd Index above 0.50 which means they are already in the category of intra-industry trade.